Relationship between x-ray emission and absorption spectroscopy and the local H-bond environment in water - Zhovtobriukh, Iurii; Besley, Nicholas A.; Fransson, Thomas; Nilsson, Anders; Pettersson, Lars G.M. (American Institute of Physics, 2018)
The connection between specific spectrum features in the water X-ray absorption (XAS) and X-ray emission (XES) spectra and the local H-bond coordination is studied based on structures obtained from path-integral molecular dynamics simulations using either the opt-PBE-vdW density functional or the MB-pol force field. Computing the XES spectrum using all molecules in a snapshot results in only one peak in the lone-pair (1b1) region while the experiment shows two peaks separated by 0.8-0.9 eV. Different H-bond configurations were classified based on the local structure index (LSI) and a geometrical H-bond cone criterion. We find that tetrahedrally coordinated molecules characterised by high LSI values and two strong donated and two strong accepted H-bonds contribute to the low energy 1b1 emission peak and to the post-edge region in absorption. Molecules with asymmetric H-bond environment with one strong accepted and one strong donated H-bond and low LSI values give rise to the high energy 1b1 peak in the emission spectrum and mainly contribute to the pre-edge and main-edge in the absorption spectrum. The 1b1 peak splitting can be increased to 0.62 eV by imposing constraints on the H-bond length, i.e. for very tetrahedral structures short H-bonds (less than 2.68 Å) and for very asymmetric structures elongated H-bonds (longer than 2.8 Å). Such structures are present, but underrepresented, in the simulations which give more of an average of the two extremes.